2015
DOI: 10.1523/jneurosci.1865-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase-1 Inhibitor-2 Is a Novel Memory Suppressor

Abstract: Reversiblephosphorylation,afundamentalregulatorymechanismrequiredformanybiologicalprocessesincludingmemoryformation,iscoordinated bytheopposingactionsofproteinkinasesandphosphatases.TypeIproteinphosphatase(PP1),inparticular,hasbeenshowntoconstrainlearningand memory formation. However, how PP1 might be regulated in memory is still not clear. Our previous work has elucidated that PP1 inhibitor-2 (I-2) is an endogenousregulatorofPP1inhippocampalandcorticalneurons(Houetal.,2013).Contrarytoexpectation,ourstudiesofc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…In line with this, Yang et al (2015) found that phosphorylated CREB levels and CREB-mediated gene expression were increased after I-2 reduction in both rats and mice (Yang et al, 2015, their Fig. 3).…”
Section: I-2supporting
confidence: 58%
See 4 more Smart Citations
“…In line with this, Yang et al (2015) found that phosphorylated CREB levels and CREB-mediated gene expression were increased after I-2 reduction in both rats and mice (Yang et al, 2015, their Fig. 3).…”
Section: I-2supporting
confidence: 58%
“…Heterozygous animals (I-2 ϩ/Ϫ ) on the other hand, were healthy and showed no abnormal phenotypes. I-2 levels in the brains of these animals were ϳ50% of those detected in wild-type littermates (Yang et al, 2015).…”
mentioning
confidence: 73%
See 3 more Smart Citations